The History of Persian Translations of English Dystopian Literature Between 1978 and 1988 in Iran: A Case Study of Novels - Khayam Nekouei, Maryam Sadat; Alinouri, Leila (Iranian Journal of Translation Studies, 2025)
Despite the intersection of Translation Studies and Persian Literature, few studies have examined the Persian translation of dystopian novels. This research investigated the Persian translations of English dystopian novels during Iran’s politically charged decade (1978–1988), spanning the Islamic Revolution (1979) and the Iran-Iraq War (1980–1988). Adopting Pym’s (2014) historiographic model, the study employed a descriptive-analytical method to analyze the quantity of translated dystopian novels, the role of translators, and the ideological motivations behind their selections. Data were extracted through content analysis of paratexts—critiques, synopses, prefaces, and translators’ notes—from all the novels published in this period. Using Pym’s (2014) paradigms of translation archaeology, historical criticism, and explanation, the study uncovered the sociopolitical influences on translational decision-making. Findings demonstrated that, despite strict censorship, translators strategically wielded dystopian literature as a tool for resistance and political critique. Translations of 1984, Animal Farm, Darkness at Noon, The Iron Heel, and This Perfect Day could not merely be linguistic conversions, but profound contextualized actions that testify to the involvement of the translators with the political realities of the era in Iran. By revealing how literary translation in repressive or transitional settings serves as a site for ideological negotiation and intellectual activism, this research advances the field of translation history.